SWOT STRATEGY: STRENGTHENING OF THE COMPETENCE OF STUDENTS OF FEBI UINSU MEDAN THROUGH MBKM PROGRAM - Syahbudi, Muhammad; Irham, Mawaddah; Indra, Ahmad Perdana; Barus, Elida Elfi (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Darma Agung (LPPM_UDA), 2023)
The Merdeka Belajar Kampus Merdeka (MBKM) program aims to improve abilities, soft skills, and hard skills. The purpose of this study is to develop the right strategy to improve the soft skills of Islamic banking study program students in the MBKM program. This study uses the SWOT analysis method to analyze internal (strengths and weaknesses) and external (opportunities and threats) factors for students that are the basis for determining strategies. The total active student population of the Islamic banking study program in this study amounted to 41 students. The data collection technique used in this study was a questionnaire. The results of this study show that the strategy carried out by the Islamic banking study program is a Turnaround or WO strategy, namely by creating a strategy that minimizes weaknesses to take advantage of opportunities with the strategy